The Analysis of Character Formation of Curiosity in Science Learning in Elementary Schools - Wulandari, Niken; Eko Nugroho, sunyoto; Lisdiana, Lisdiana (Journal of Primary Education, 2020)
Embedding integrated character in learning is still a problem in implementation in schools, especially the development of the value of curiosity in science learning. This research aims to describe the value of the character of students curiosity in science learning; analyze the signs of curiosity character values that emerge; and know the obstacles experienced when applying the character of curiosity in the science learning process. This research used a qualitative research method, namely, case study research. Research in Elementary School 4 Besito Kudus. Research respondents included 16 fifth grade students and fifth-grade teachers. Data collection using interviews, observation, questionnaires, and documentation. Triangulation is used as a data validity test. The process of data analysis through the process of data reduction, data presentation, and conclusions. The results showed that the enthusiasm of students in the scientific process, enthusiastic about looking for answers; the emergence of the character of curiosity in science learning is carried out by the teacher in teaching by providing practice; and different backgrounds affect the character of children and the role of teachers and parents in encouraging student curiosity, so it can be concluded that the formation of curiosity characters in science learning through a scientific approach in elementary school, it is necessary to get used to teaching and learning activities.